Character design for a motion comic from textual classical Malay narratives discursive descriptions: creativity in an Islamic perspective / Muhamad Azhar Abdullah, Hafizah Rosli and Voviana Zulkifli - Abdullah, Muhamad Azhar; Rosli, Hafizah; Zulkifli, Voviana (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Characters in classical Malay textual narratives are predominantly complemented by descriptive qualities of their personalities with atypical portrayals of the physique which are not accentuated by any illustrations. Visual adaptation of the characters for new presentation would require artists to illustrate from the discursive descriptions for character design. Most contemporary references on drawing for character design emphasize the physical or exoteric ascriptions rather than the harmony between inspiration and spiritual or the esoteric perceptions. Although such references encourage novice artists to learn and search for inspiration (ilham), which involves the inner self in the thinking process, the latter is hardly explored, especially through the Islamic perspective. Research has shown that creativity is a skill that can be learned. This article provides a conceptual value to the field of character design for motion comics from an Islamic perspective through content analysis of classical Malay textual narratives and the meanings from various chapters in the Holy Quran which include a range of elements in creativity. It is established that Islam promotes creativity through certain practices, including using the heart or qalb which is also known as the seat of the al-‘aql or intellect, and practising tafakkur, or immersing the self in deep contemplation, as suggested in the Quran.